Bunkring av fartyg med LNG - Kommer det vara lönsamt att utföra med ett bunkerfartyg i Göteborg - Skagenområdet? - Hast, Henrik; Åsegård, Stefan (My University, 2014)
Stricter environmental requirements for shipping have led to vessel operators are regarding LNG as an alternative marine fuel. LNG has been pointed out as the most environmental friendly marine fuel and will meet the more strict requirements on sulfur emissions. For LNG to be an option, it is supposed that there is a supply chain to the end user. This study intends to investigate whether it will be profitable to use a bunkering vessel for delivery of LNG to the marine end users in Gothenburg - Skaw area. A case study was used as the method for answering the research issue. Primary data were collected through semi-structured interviews from informants who possess considerable knowledge of the subject and represent different parts of the market. Furthermore, secondary data from official reports were used to analyze primary data through triangulation. The study indicates that it will be profitable to deliver LNG by ship to marine customers. It requires more vessels using LNG as a marine fuel to increase the demand and raise the utilization rate for the bunkering vessel to become profitable. The development of vessels of which propulsion is based on LNG and thus demand for LNG will increase in line with the requirements of sulfur emissions are tightened globally. However, to predict when it will be profitable is not possible.
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport